2021
DOI: 10.1155/2021/6429197
|View full text |Cite
|
Sign up to set email alerts
|

I‐κB Kinase‐ε Deficiency Attenuates the Development of Angiotensin II‐Induced Myocardial Hypertrophy in Mice

Abstract: I-κB kinase-ε (IKKε) is a member of the IKK complex and a proinflammatory regulator that is active in many diseases. Angiotensin II (Ang II) is a vasoconstricting peptide hormone, and Ang II-induced myocardial hypertrophy is a common cardiovascular disease that can result in heart failure. In this study, we sought to determine the role of IKKε in the development of Ang II-induced myocardial hypertrophy in mice. Wild-type (WT) and IKKε-knockout (IKKε-KO) mice were generated and infused with saline or Ang II for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Activation of NF-κB–dependent transcription has been found in numerous heart diseases, including hypertrophic cardiomyopathy, myocardial infarction, ischemia/reperfusion injury, and so on ( Jones et al, 2005 ; Hall et al, 2006 ; Baldwin, 2012 ; Kumar et al, 2012 ; Maier et al, 2012 ; Cao et al, 2021 ). In our previous studies, the role of IKKε in atherosclerotic lesions and aortic stenosis has been suggested ( Cao et al, 2013 ; He et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of NF-κB–dependent transcription has been found in numerous heart diseases, including hypertrophic cardiomyopathy, myocardial infarction, ischemia/reperfusion injury, and so on ( Jones et al, 2005 ; Hall et al, 2006 ; Baldwin, 2012 ; Kumar et al, 2012 ; Maier et al, 2012 ; Cao et al, 2021 ). In our previous studies, the role of IKKε in atherosclerotic lesions and aortic stenosis has been suggested ( Cao et al, 2013 ; He et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, the role of IKKε in atherosclerotic lesions and aortic stenosis has been suggested ( Cao et al, 2013 ; He et al, 2019 ). The IKKε-KO could attenuate mice’s pathological progression in Angiotensin II-Induced Myocardial Hypertrophy and aortic valve thickening ( He et al, 2019 ; Cao et al, 2021 ). However, the role of IKKε in dilated cardiomyopathy is unclear.…”
Section: Introductionmentioning
confidence: 99%